ALUMINUM SUBSTITUTION IN MGSIO3 PEROVSKITE: INVESTIGATION OF MULTIPLE MECHANISMS BY 27AL NMR - Stebbins J.F.; Kojitani H.; Akaogi M.; Navrotsky A. (My University, 2003)
In the Earth's mantle, the mechanism(s) of solid solution of Al in MgSi03 perovskite strongly impacts its thermodynamic and transport properties. We present Al NMR data for perovskite samples of nominal composition Mg(SiO.9Al0.1)02.95, to test a mechanism by which Al substitutes at the octahedral Si sites, leaving a corresponding number of O-site vacancies. We find evidence for this process in a significantly greater peak area for Al at B (Si) sites vs. A (Mg) sites in the structure, and the possible identification of a small concentration of five-coordinated Al adjacent to such vacancies. However, substitution of Al3+ at the A sites remains significant. As in perovskite-type technological ceramics, O-atom vacancies may play an important role in enhancing ion mobility and the dissolution of water.
Keywords: ALUMINUM; NUCLEAR MAGNETIC RESONANCE; NMR; perovskite